Kebijakan Pemerintah DKI Jakarta Menangani Pandemi COVID-19 - Meilinda Triana Pangaribuan; Adis Imam Munandar (Departemen Ilmu Pemerintahan Fisip Unhas, 2021)
Post Covid 19 was declared as a national disaster non-natural, central and local government try to do various efforts and policies to handle Covid 19. One of the areas in Indonesia which has number of cases Covid 19 highest is Jakarta. The increase in cases Covid 19 very influential and have an impact significant enough for a variety of important sectors such as economy, education, health in Jakarta. Various policies and efforts have been made by the government of DKI Jakarta, such as policy Restrictions on Large-Scale Social (PSBB) to reduce the cases Covid 19 in Jakarta. However the increase in cases Covid 19 in Jakarta has not shown a significant decline. This study aims to analyze the policies and efforts taken by the government of Jakarta to handle Covid 19. The research is qualitative research with descriptive method of analysis and data collection techniques using literature study. The results of the study showed that the policy and efforts made are not yet fully effective in handling Covid 19 in Jakarta. The Obstacles in handling comes from the non-compliance communities and weak coordination of central and local government.